2016
DOI: 10.1016/j.jmii.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase genetic polymorphisms and susceptibility to Kawasaki disease in Taiwanese children

Abstract: Our results suggest that G allele of MPO -463G>A polymorphism is a potential genetic marker for KD risk in Taiwanese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The findings of numerous different studies have shown that several factors induce the formation of CRC, included genetic and epigenetic alterations (28,29). Some of these gene alterations can be applied as biomarkers for cancer diagnosis and provide strategies for cancer therapy (30). The human ANP32A gene is expressed differently in different tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of numerous different studies have shown that several factors induce the formation of CRC, included genetic and epigenetic alterations (28,29). Some of these gene alterations can be applied as biomarkers for cancer diagnosis and provide strategies for cancer therapy (30). The human ANP32A gene is expressed differently in different tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, high levels of MPO correlate with the prevalence of certain autoimmune diseases. Downregulation of MPO expression has been associated with incidence and se-verity of lupus erythematodes [38], Kawasaki's disease [39], inflammatory bowel disease [40] and eosinophilic granulomatosis [41]. About half of the patients with eosinophilic granulomatosis showed perinuclear anti-neutrophil cytoplasmatic antibodies (pANCA) directed against MPO.…”
Section: Introduction Mpo Conservation Across Species Maturation In Myeloid Progenitors and Its Role In Immune Responsesmentioning
confidence: 99%
“…21 Studies of MPO polymorphisms have mainly concentrated on the -463G>A polymorphism (GenBank ID: rs2333227), and a recent case-control study suggested that the G allele of this polymorphism may be a possible genetic risk factor for KD. [22][23][24] Additionally, SLC11A1 can modulate the interactions between macrophages and interferon-c derived from bacterial lipopolysaccharide and/or natural killer cells or T cells. 24 A previous study demonstrated that allele 1 of the 5' promoter (GT)n repeat in the SLC11A1 gene was related to KD.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Additionally, SLC11A1 can modulate the interactions between macrophages and interferon-c derived from bacterial lipopolysaccharide and/or natural killer cells or T cells. 24 A previous study demonstrated that allele 1 of the 5' promoter (GT)n repeat in the SLC11A1 gene was related to KD. 25 MMP9 has been implicated in various pathological situations, including tumor metastasis, KD, inflammation, and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%